“Effectiveness of Antoxidant Treatments in Restoring Composite Bond Strength after Tooth Bleaching: An In Vitro Comparative Study ” - S. kore, Ajay .; Kararia, Nitin; Sharma, Deepak Kumar; Prathapan, Athira; Bajad, Akash; Gupta, Ashish (Journal of Neonatal Surgery, 2025)
Background: Tooth-whitening using hydrogen peroxide weakens the strength of resin-enamel bonds because of the residual free radical oxygen that prevents polymerisation of the acid bond. Use of antioxidants could help address the effects to a large extent through the elimination of the radical species, resulting in the recovery of bonding. Objective: To compare the effectiveness of Proanthocyanidin (PA) a in restoring composite bond strength to bleached enamel. Methods: This in-vitro study considered 84 upper incisors divided into four groups that included a control, a bleached control, bleached-potassium aluminium phosphate (PA) mix, and. Antioxidants were done after bleaching with 35 per cent hydrogen peroxide. Shear bond strength (SBS) was evaluated by a universal testing machine and the failure modes were analysed by scanning electron microscopy (SEM). Results: Antioxidants improved SBS significantly (p<0.05), with PA restoring values close to unbleached enamel. SEM revealed more cohesive failures in PA-treated specimens, indicating stronger adhesion. Conclusion: Application of an antioxidant immediately after tooth bleaching prevents the reduction in bond strength that is commonly encountered. In this context, the proanthocyanidin has displayed greater efficacy